Use of medicinal plants in indigenous communities settled in a piedmont evergreen forest of Santa Clara canton, Ecuadorian Amazon - Andrade Yucailla, Sandra Estefanía (2019)
Indigenous peoples have a fundamental role in knowledge and conservation of the biodiversity of medicinal plants, the  objective of the work was to identify the use of medicinal plants since ethnobotany is a tool that allows to diagnose its application in traditional phytotherapy in Santa Clara, also for its central location in the Amazon belongs to the evergreen Piemontano forest. The study information was based on a survey that was applied to 30 families from the Rey de Oriente and San Juan de Piatua communities who practice phytotherapy; Among the questions of the use of medicinal plants were (name, method of preparation, part used and dosage) the plants were grouped according to the use of the diseases and the most important species were defined; The 10 most frequent plants are Uncaria  tomentosa  (cat's claw), Ocimum campechianum (basil), Bryophyllum pinnatum (air leaf), Scoparia dulcis (tiatina), Justicia pectoralis (linden), Plantago major (plantain), Ilex guayusa (guayusa ), Urera laciniata (napi nara), Aerva sanguinolenta (escancel), Chenopodium ambrosioides (paico), for different diseases, 25 species of medicinal plants were identified, of which the leaves are the most used part of the plant with 70% and the mode of preparation is by infusion (64%), 80% of the respondents were men who dominate the ancestral practice and have ages between 18 - 70 years and 50% are illiterate, the ancestral knowledge of plants was recorded Medicines in health-disease function that afflict the Amazonian rural populations.